ROMS+BEC coupled model output for the northern Benguela upwelling system - Elisa Lovecchio (PANGAEA, 2025)
Data from a coupled ROMS+BEC (Shchepetkin and McWilliams, 2006; Moore et al. 2013; Frischknecht et al. 2018) hindcast simulation for February-June 2018. The coupled model was run on a northern Benguela upwelling system regular grid of horizontal resolution of 3.3 km, using a vertical sigma-layer coordinate. Original model output was saved in the form of 3D daily means. These NetCDF files contain model output that was post-processed for the creation of figures included in a submitted manuscript (preliminary title "Mesopelagic particle layers of the hypoxic northern Benguela are shaped by diel vertical migration, zooplankton communities and near shore currents." by Lovecchio et al.). A description of the model setup and an evaluation of the model are provided in the manuscript and its supplement. This model run was created to complement and upscale in-situ glider SL405 data collected in the same period in the northern Benguela (published here doi:10.1594/PANGAEA.938221). ROMS-BEC_data_Figure8a_FigureSA6.nc file contains day-mean modelled particulate organic carbon, oxygen and velocities subsampled in proximity of glider SL405 for the entire model output period February-June 2018. ROMS-BEC_data_Figure8bcd.nc contains 2D fields of particulate organic carbon, velocities and oxygen averaged between 200-300 m depth or sliced vertically at 18S, in the proximity of the glider SL405 position, for day 08 May 2018 of the model simulation. ROMS-BEC_data_FigureSB* files contain February-June 2018 meanmodelled temperature, salinity, chlorophyll, sea surface height and oxygen fields used for model evaluation.